Measuring prevailing practices of healthcare professional on electronic health record through the lens of Iraq - Murtaja Ali Saare; Alia Ahmed Mahdi; Saima Anwar Lashari; Sari Ali Sari; Norhamreeza Abdul Hamid (Institute of Advanced Engineering and Science, 2021)
Paper based approach to clinical documentation such as handwritten notes among health care providers are cause of errors in medical field. Therefore, health record system needs to be replaced with electronic health record (EHR). Many health professionals in developing countries specifically in Iraq refuse to use the systems implemented for their benefits due to many reasons. Thus, the use of electronic services is important for successful electronic health implementations. Therefore, this study is intended to identify the main factors affecting the intention of use of the electronic health record in Iraq. Health professional staff who work in the main hospital in Dhi-Qar is chosen because this province is the first local province that implemented many electronic projects. The present study examined use of user acceptance of technology, based on the technology acceptance model (TAM). Moreover, the quantitative method approach for data collection using survey from staff who work in the main hospital in Dhi-Qar. Data was analyzed using Structural Equation Modeling using AMOS. The results indicated significant relationship between Ease of Use, Usefulness, Usefulness, Attitude, and Intention of use of EHR. These finding have implementation for decision makers in Iraq government to improve future implementation of e-health services.